Stress Management Workshop for Maternal and Child Health Services - Aryati, Ana Sofia (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study addresses work stress as a significant psychosocial issue in maternal and child health services within hospitals. It investigates the necessity of stress management improvements for enhancing employee well-being and reducing negative work behaviours such as absenteeism and turnover. Method: The research was conducted through a Stress Management Workshop at X Maternity and Children's Hospital (RSIA) in Malang City. The methodology included interactive sessions on recognizing stress, understanding its impacts, problem-solving in stressful situations, and practicing relaxation techniques. Practical Applications: The findings highlight the practical application of stress management strategies in real-world healthcare settings. Implementing these strategies can lead to better self-development, improved employee well-being, and more positive work behaviours, benefiting both the employees and the hospital's operational efficiency. Conclusion: The study concludes that stress management is crucial for maternal and child health service employees. The workshop successfully increased awareness and understanding of stress management, contributing to better self-development and positive work behaviours, thereby addressing the identified psychosocial problem.